Muscle Sympathetic Nerve Activity Is Associated with Liver Insulin Sensitivity in Obese Non-Diabetic Men - Chen, Daniel L. T.; Brown, Rachael; Liess, Carsten; Poljak, Anne; Xu, Aimin; Zhang, Jialiang; Trenell, Michael; Jenkins, Arthur; Chisholm, Donald; Samocha-Bonet, Dorit; Macefield, Vaughan G.; Greenfield, Jerry R. (Frontiers in Physiology, 2017)
Introduction: Muscle sympathetic nerve activity (MSNA) may play a role in insulin resistance in obesity. However, the direction and nature of the relationship between MSNA and insulin resistance in obesity remain unclear. We hypothesized that resting MSNA would correlate inversely with both muscle and liver insulin sensitivity and that it would be higher in insulin-resistant vs insulin-sensitive men. Materials and methods: Twenty-two non-diabetic obese men aged 48 ± 12 years were studied. Two-step (15 and 80 mU/m2/min) hyperinsulinaemic-euglycaemic clamps were performed using deuterated glucose to determine liver and muscle insulin sensitivity. Clinical and metabolic parameters were assessed. MSNA was measured via a microelectrode inserted percutaneously into the common peroneal nerve. Results: MSNA burst frequency correlated inversely with liver insulin sensitivity (r = -0.53, P = 0.02) and positively with the hepatokines, C-reactive protein (CRP) and fibroblast growth factor (FGF)-19 (r = 0.57, P = 0.006 and r = -0.47, P = 0.03, respectively). MSNA burst frequency was lower in Liversen compared to Liverres (27 ± 5 vs. 38 ± 2 bursts per minute; P = 0.03). Muscle insulin sensitivity was unrelated to MSNA. Discussion: Sympathetic neural activation is related to liver insulin sensitivity and circulating hepatokines CRP and FGF-19 in non-diabetic obese men. These results suggest a potential hepato-endocrine-autonomic axis. Future studies are needed to clarify the influence of MSNA on liver insulin sensitivity in men.